2016
DOI: 10.1007/s40071-016-0134-1
|View full text |Cite
|
Sign up to set email alerts
|

Insights into kisspeptin- and leptin-signalling on GnRH mRNA expression in hypothalamic organ cultures of immature pikeperch Sander lucioperca

Abstract: Two types of gonadotropin-releasing hormones (GnRH) were identified as gnrh1 and gnrh2 in pikeperch Sander lucioperca. The administration of rodent leptin on hypothalamic organ cultures of immature pikeperch resulted in significantly elevated levels of gnrh2, but not in gnrh1 mRNA, whereas kisspeptin-10 administration did not affect gnrh1 or gnrh2 expression. These results represent preliminary insights into leptin-GnRH-signaling on a hypothalamic level in fish, potentially coupling fat metabolism and the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…The cart -dependent regulation of gnrh secretion by activated leptin signal had been already reported in rat 71,72 . Also, in a Perciforme species, it has been shown that leptin increases the brain expression of gnrh2 , but not gnrh1 73 . Our results indicate that the functional leptin signal induces the expression of anorexigenic gnrh2 in zebrafish, in normal feeding condition.…”
Section: Discussionmentioning
confidence: 96%
“…The cart -dependent regulation of gnrh secretion by activated leptin signal had been already reported in rat 71,72 . Also, in a Perciforme species, it has been shown that leptin increases the brain expression of gnrh2 , but not gnrh1 73 . Our results indicate that the functional leptin signal induces the expression of anorexigenic gnrh2 in zebrafish, in normal feeding condition.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, the cart -dependent regulation of Gnrh secretion by activated leptin signal had been demonstrated in rat brain as well (Lebrethon et al 2000 ; Parent et al 2000 ). Moreover, in Sander lucioperca , a perciform fish species, it is shown that leptin induces the brain expression of gnrh2 (Schaefer and Wuertz 2016 ), and in goldfish, gnrh2 has been reported to be a downstream transcriptional target of crh (Kang et al 2011 ). In response to feeding, crh and gnrh2 have been recently reported to have similar expression patterns in Schizothorax davidi (another Cypriniformes species) (Yuan et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%